AUGUST ACTIVITY REPORT - LANE, WES (Tufts Archival Research Center, 2007)
Marginalia; Letter from Wes Lane to Susan Stuntz regarding the August 1990 Activity Report. Announces recently introduced anti-tobacco ordinances, one proposing an indoor smoking ban in Minneapolis city buildings, and the other a state-wide ban on cigarette vending machines. Reveals that city council members promised not to vote for the various city indoor smoking bans, but will vote for the vending machine ban.